If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3y+7=-6/56
We move all terms to the left:
3y+7-(-6/56)=0
We get rid of parentheses
3y+7+6/56=0
We multiply all the terms by the denominator
3y*56+6+7*56=0
We add all the numbers together, and all the variables
3y*56+398=0
Wy multiply elements
168y+398=0
We move all terms containing y to the left, all other terms to the right
168y=-398
y=-398/168
y=-2+31/84
| 8x+0=26 | | 144+x^2=324 | | -2x+28=14 | | -72-13x=33-10x | | -2/3x+1/3+x=2/55 | | 7/5x=50 | | 24.5x-2+1/2=14+1/2x+17.5 | | -8+3x=4-x | | 5-10(2x+9)=45-7x | | 2/25=m/125 | | q+5.5=17.3 | | 7-4(5+6)=z | | -4(6x+10)=-2(12x+20) | | -14-3x=14+x | | 40=32+w | | 23x^2-124x+63=0 | | 8/5x+3=13/5 | | 4x+4-6x=2 | | 9a-7a=-6 | | 4((2z-3(6-4z))-12(z-1)=4 | | 9x-5+8=6 | | 1.1=1/x | | 12x-100=15x-40 | | 3w/7=18 | | 3w-7=18 | | 4-5r/3=-2 | | 5=r+6/5 | | x=7x5−4x4+7x−15 | | 12x-100=15-40 | | v-6.37=4.58 | | -13=x/5-10 | | x=4x−6x8 |